Decontamination protocol of the macroalga Bostrychia binderi Harvey (Rhodophyta) for unialgal cultures and laboratory studies - Borburema,Henrique Douglas dos Santos (2021)
ABSTRACT This study aimed to test the effectiveness of physical and chemical procedures for surface decontamination of Bostrychia binderi Harvey. For this, thalli were washed and immersed in chemical solutions (5% liquid detergent, 1% povidone iodine and 0.2% sodium hypochlorite) at different times and combinations. After treatments the thalli were cultivated in laboratory to verify possible negative effects caused by the procedures to alga. Contaminating organisms in the algal culture medium were quantified at the end of cultivation. Washing, spraying, removal of macrofauna individuals with tweezers, thalli immersion in 5% liquid detergent for 60 seconds, after in 0.2% sodium hypochlorite for 2 minutes were effective procedures to eliminate all contaminants analyzed. Thalli immersion in 1% povidone iodine did not affect negatively the thalli growth, whereas immersion in 0.2% sodium hypochlorite for 5 minutes affected. For establishment of Bostrychia unialgal cultures we recommend the protocol proposed in this study.